Educommunication 2.0: a key tool in sustainable marketing strategies in the tourism sector. (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2021)
This research focuses on Educommunication 2.0 as a tool in service of sustainable marketing in the tourism sector. It begins with the potential of marketing for creating specific behaviors, especially sustainable ones. Sustainability is the link between marketing and social and environmental issues given its triple dimension. In this sense, it acts as a connection point between the interests of tourism organizations and those of their stakeholders. Regarding the influence of marketing on behaviors, Educommunication 2.0 emerges as an efficient tool that has been scarcely researched despite its communicational and educational advantages in achieving strategic objectives in this field. Thus, this descriptive research is proposed to verify these advantages in the tourism sector, as it is an industry particularly sensitive to sustainability. After concluding about marketing's contribution to it, the in-depth literature review suggests the need to consider Educommunication 2.0 as an essential tool in sustainable tourism marketing strategies in order to generate eduprosumers: tourists who, having learned responsible behaviors, intentionally share, spread, and promote them.
Keywords: Educomunication; sustainable marketing; tourism sector